Pentingnya Penerapan Digital Marketing Dalam Proses Memajukan UMKM Di Daerah Jakarta Selatan - Sri Astuti; Bela Hemalia Putri; Firli Agustini; Indratni Khair (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In an increasingly advanced world, technology can be realized by micro, small and medium business entities (MSMEs). One of the marketing media that is currently in great demand by MSMEs to support sales and promotions is digital marketing. This progress is considered very useful as a business marketing strategy which is also carried out by MSMEs. Use of e-business, e-commerce and social media to support MSMEs in the areas of promotion, marketing and sales. The purpose of this research is to identify the business income obtained and the importance of implementing digital marketing after using digital marketing. The results of this research found the importance of implementing digital marketing in the process of advancing micro, small and medium enterprises (MSMEs). So Digital Transformation can help organizations change the way they operate, increase their ability to adapt to change, and improve the quality of their services.